ANALISIS KEBIJAKAN PESANTREN TENTANG PENDIDIKAN DALAM MASA PSBB PANDEMI COVID-19 - Achmad Beadie Busyroel Basyar; Moh. Halim (Pascasarjana Institut Agama Islam Al-Qolam, 2022)
The Covid-19 pandemic that hit the world, it has been almost 2 years that Indonesia has also spread Covid-19, with the presence of Covid-19 there have been changes to the teaching and learning process activities. Online learning activities have become a choice of the ministry of education and culture to prevent and break the chain of spreading the Covid-19 virus increasingly widespread. This research aims to find out how Government policies and their implementation are carried out as well as the obstacles by Islamic boarding schools in carrying out prevention. the spread of the Corona 19 Virus in the Islamic Boarding School environment in teaching and learning activities. This type of research is a descriptive study using qualitative methods. Data collection techniques in this study are interviews with several informants, observation ,. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Government's policy on preventing the spread of Corona 19 Virus in Islamic boarding schools or dormitories. It is not entirely the policies of the central and local governments that are carried out by the Islamic boarding schools / dormitories because there are many obstacles that are not implemented among the pesantren. The circular issued by the Islamic Boarding School is based on the existence of a circular or government decision regarding the prevention of the spread of the Corona 19 Virus with and for the continued implementation of teaching and learning activities at the Islamic boarding school. Keywords: Islamic Boarding School Policy, Covid Pandemic 19